Full-biodegradable composite film and preparation method thereof

By adopting a three-layer structure, the dense barrier protective layer is formed by using modified calcium carbonate, PLA, PBAT and modified montmorillonite, which solves the shortcomings of the existing biodegradable packaging film in terms of strength, toughness and barrier properties, and achieves an efficient and economical packaging solution.

CN119526864AActive Publication Date: 2025-02-28CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311116288.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-02-28
Estimated Expiration
2043-08-31

AI Technical Summary

Technical Problem

The existing biodegradable packaging films have shortcomings in terms of high strength, high toughness, high barrier properties and cost, and are difficult to meet the high-end packaging needs of high-tech fine instruments, food and pharmaceutical industries.

Method used

The fully biodegradable composite membrane with a three-layer structure is 1:(1-1.5):1, and consists of modified calcium carbonate, PLA, PBAT and epoxy chain extender, modified montmorillonite, PPC, PLA, and PBAT respectively. Through the cooperation of modified montmorillonite and PPC, a dense barrier protective layer is formed to improve the compatibility and mechanical properties of the film.

Benefits of technology

It has achieved high strength, high toughness, and high barrier properties, and is low in cost and is suitable for high-end packaging fields in the high-tech fine instruments, food and pharmaceutical industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004425279760000131
    Figure BDA0004425279760000131
  • Figure BDA0004425279760000141
    Figure BDA0004425279760000141
  • Figure BDA0004425279760000301
    Figure BDA0004425279760000301
Patent Text Reader

Abstract

The invention provides a full-biodegradable composite film and a preparation method thereof. The full composite membrane comprises an outer layer, a middle layer and an inner layer, wherein the outer layer comprises modified calcium carbonate, PLA, PBAT and an epoxy chain extender; the middle layer comprises modified montmorillonite, PLA (polylactic acid), PBAT (poly (butylene adipate-co-terephthalate)), PPC (polypropylene carbonate) and an epoxy chain extender; the inner layer comprises PLA (polylactic acid), PBAT (poly (butylene adipate-co-terephthalate)), an epoxy chain extender and an optional anti-blocking agent. The preparation method of the raw materials of the middle layer comprises the following steps: (i) dividing an epoxy chain extender used by the middle layer into an epoxy chain extender A and an epoxy chain extender B, and mixing PPC, modified montmorillonite and the epoxy chain extender A to prepare a first master batch of the middle layer; (ii) mixing PLA, PBAT and an epoxy chain extender B to prepare a middle-layer second master batch; and (iii) uniformly mixing the middle-layer first master batch and the middle-layer second master batch, extruding and granulating to obtain a middle-layer raw material. The full-biodegradable composite film prepared by the preparation method disclosed by the invention is good in uniformity and quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of packaging films, and in particular relates to a fully biodegradable composite film and a preparation method thereof. Background Art

[0002] With the development of economy and the improvement of people's living standards, people's requirements for commodities are getting higher and higher, and the development of packaging materials driven by this is changing with each passing day. Among them, there is a relatively large demand for the barrier properties of packaging materials. The packaging of food, medicine and some high-tech precision instruments requires packaging materials to have good gas barrier and moisture barrier properties. On the one hand, the penetration of oxygen and water vapor may affect the shelf life or use cycle of the product in the package and shorten the life of the product. On the other hand, the leakage of packaging materials may cause pollution and corrosion to the shelves, affecting people's consumption demand for products. Especially in the food and pharmaceutical industries, the entry of oxygen and water vapor will pose a fatal threat to the quality of commodities and endanger human health. As synthetic polymers commonly used in barrier packaging, such as polyethylene, polypropylene plastics, EVOH resin series barrier films, active barrier films, PET bottles, etc., although they have good barrier properties against water vapor and moisture, the corresponding plastic products bring great convenience to people's lives, while a large amount of plastic waste also brings huge environmental problems. Therefore, the development of green, healthy, sustainable, widely used raw materials and excellent gas barrier properties of fully biodegradable composite materials has important significance and great development prospects.

[0003] Biodegradable plastics have formed an industrial scale in the Chinese market, and the main ones occupying a large market share are polylactic acid (PLA), polybutylene adipate / terephthalate (PBAT) and polypropylene carbonate (PPC). PLA has high tensile strength and elastic modulus, but it is more brittle than tough, its high-temperature mechanical properties are unstable, it is very sensitive to temperature changes, and its processing range is narrow. PBAT has good mechanical properties and toughness, high processing properties and thermal stability, but low strength. PPC has certain gas barrier properties, but PPC is an amorphous structure, the molecular chain is flexible and the interaction force is small, which makes the thermal properties of the material poor, resulting in poor high-temperature dimensional stability of the product and high brittleness at low temperatures, so its large-scale application has not yet made a breakthrough.

[0004] At present, in order to meet the multiple quality indicators of biodegradable plastic shopping bags, a variety of materials are usually blended for film blow molding. However, during the blow molding process, it is found that the compatibility between degradable materials is poor, making it difficult to blow mold continuously. Generally, compatibilizers are added to improve the compatibility and mechanical strength of the raw materials. At present, although there are some research applications of fully biodegradable packaging bags, compared with traditional plastic bags, they have great deficiencies in high strength, high toughness, high barrier properties, and cost.

[0005] Chinese patent application CN100999587A discloses a fully degradable film with excellent heat resistance, non-anisotropic tear resistance and flexibility and a method for preparing the material thereof. The film composition mainly comprises polylactic acid and aliphatic polyester and corresponding plasticizers and additives. Its defects are: from the perspective of the composition components, polylactic acid and aliphatic polyester cannot achieve good compatibility, and the obtained flexible film has poor heat resistance and puncture resistance. When used at high temperatures, the film is prone to creep deformation, which affects normal use.

[0006] Chinese patent application CN02801476.6 discloses a biodegradable resin polymer, film and agricultural film, wherein the polymer is composed of fatty acid polyester and polylactic acid polymer. The defect is that the content of polylactic acid in the components is less than 20 parts of the total amount, and the obtained film has the defects of low mechanical strength and poor tear resistance.

[0007] Chinese patent application CN104387732A discloses a transparent tear-resistant polylactic acid biodegradable film and its preparation method, wherein the mixture is mainly composed of polylactic acid, toughening agent, plasticizer, lubricant, and opening agent. Its defects are: the polylactic acid film has poor toughness and is easy to crack. The added plasticizer is a small molecule substance and has the defect of easily overflowing from the polymer. In addition, the toughening agent polybutylene carbonate has poor thermal properties and is easy to degrade during the processing process, resulting in reduced mechanical properties of the film, and poor puncture resistance and rigidity-toughness balance of the film.

[0008] Chinese patent application CN104893199A discloses a fully degradable plastic film with a wide temperature range and strong toughness. Its defects are: the composition has many components, poor compatibility and poor strength-toughness balance, and the polyvinyl alcohol in the component is not specifically defined, which has the defect of safety uncertainty.

[0009] Chinese patent application CN 105462124 A discloses a bio-based plastic and a preparation method thereof. The defect is that the mixed solvent used contains benzene substances, which are easily precipitated during the blow molding process and cannot meet the requirements of green processing technology.

[0010] Chinese patent application CN 106633722 A discloses a tear-resistant and high-toughness biodegradable material. The invention adopts a two-step method to prepare PBAT / nanomaterial one-step material respectively; the reaction plasticization is completed in the front section of the extruder, and the reactive chain extension and volume expansion are realized in the middle and rear sections. It has the advantages of high tear strength and good flexibility. Its disadvantages are: there are many components, the processing steps are cumbersome, and the puncture resistance of the film is not well presented.

[0011] Chinese patent application CN201611028759.6 discloses "a tear-resistant and high-toughness biodegradable material and its preparation method", which is a PLA / PBAT binary alloy material. The tear resistance and toughness are mainly achieved by PBAT, plasticizer and other auxiliary materials, and the toughness is greatly improved. Its defects are: the tear resistance is not significantly improved, and the tensile strength is greatly reduced.

[0012] Chinese patent application CN201510646442.8 discloses a "PLA / MMT degradation enhancement masterbatch blended modified PLA / PBAT composite material and its preparation method". The invention uses polylactic acid (PLA), poly(terephthalic acid-adipate-butylene glycol) copolyester (PBAT) and PLA / MMT degradation enhancement masterbatch as raw materials, and evenly mixes 10-90 parts of PLA, 10-90 parts of PBAT, and 5-30 parts of PLA / MMT degradation enhancement masterbatch, and melt blends and modifies PLA / PBAT to prepare a PLA / PBAT composite material, wherein the PLA / MMT degradation enhancement masterbatch is prepared by using an intercalation agent and an intercalation aid to prepare an organic montmorillonite by ion exchange, increasing the interlayer spacing between montmorillonites, and then intercalating the monomer or polylactic acid molecular chain into the interlayer of montmorillonite by melt in-situ polymerization. Its defect is that its elongation at break is 16.23%, which is not suitable for the field of express packaging films, because this elongation at break is far from the requirements of this application field.

[0013] Chinese patent application CN201510380483.7 discloses "a method for preparing PLA / PBAT / PPC composite modified materials by reactive extrusion". The weight ratios are PLA5-35, PBAT30-55, PPC5-15, and the plasticizer content is 0.5-2 weight parts based on 100 weight parts of PPC; based on 100 weight parts of PBAT, the initiator content is 0.01-0.08 weight parts, the co-reactant content is 0.01-0.05 weight parts, the grafted monomer content is 1-3 weight parts, and the anti-aging additive content is 0.5-1.5 weight parts. This invention uses a reactive twin-screw extruder to graft PBAT and then blend it with PLA and PPC to prepare a ternary alloy composite material. The grafted PBAT plays a capacity-increasing role, and the toughness of the composite material is improved to a certain extent. Its defects are: the tear resistance is not significantly improved, and due to the low tensile strength and poor heat resistance of PPC, the tensile strength of the composite material is even lower than that of the PLA / PBAT binary composite material, and the heat resistance is also worse.

[0014] Chinese patent application CN201310192664.8 discloses "a PLA / PBAT biodegradable composite material", which is made of 60% to 75% polylactic acid, 60% to 75% polybutylene adipate / terephthalate, 1% to 5% polycaprolactone, 5% to 15% ethylene-vinyl acetate copolymer, 1% to 5% ethylene-vinyl acetate copolymer and polylactic acid graft copolymer, and 1% to 10% vegetable oil polyol. Its defect is that ethylene-vinyl acetate copolymer is a petroleum-based material, does not have low-carbon environmental protection characteristics, and is not biodegradable in the natural environment, so the low-carbon biodegradability of the invention is not good.

[0015] Chinese patent application CN113881110A discloses a fully biodegradable composite film, a preparation method and a courier bag thereof. Specifically, the composite film comprises a first layer, a second layer and a third layer stacked in sequence; the first layer and the third layer comprise: 70 to 90 parts by weight of plasticized starch, 5 to 15 parts by weight of polylactic acid, 5 to 15 parts by weight of polycaprolactone and 0.02-0.1 parts by weight of chain extender; the second layer comprises: 60 to 80 parts by weight of polypropylene carbonate, 5 to 15 parts by weight of poly(adipate / terephthalate)butylene glycol, 5 to 15 parts by weight of polycaprolactone and 0.02 to 0.1 parts by weight of chain extender. Its defect is that the first and third layers add a large specific gravity of plasticized starch, which has poor compatibility, resulting in poor impact resistance of the film, and the prepared packaging bag is prone to rupture during use.

[0016] In summary, in view of the shortcomings of the existing technical means, the present invention aims to provide a fully biodegradable film with high strength, high toughness and high barrier properties. Summary of the invention

[0017] The primary purpose of the present invention is to overcome the defects in the above-mentioned prior art and provide a fully biodegradable film composition with high strength, high toughness, high barrier performance and low cost and a preparation method thereof. The fully biodegradable film composition of the present invention can be widely used in high-tech precision instrument packaging, food and pharmaceutical industries and other high-end packaging fields with high barrier requirements.

[0018] Specifically, the present invention provides a fully biodegradable composite film, which comprises an outer layer, a middle layer and an inner layer arranged in sequence from the outside to the inside, wherein the thickness ratio of the outer layer, the middle layer and the inner layer is 1:(1-1.5):1; wherein, in parts by weight:

[0019] The outer layer comprises: 30 to 40 parts of modified calcium carbonate, 20 to 40 parts of PLA, 20 to 50 parts of PBAT, and 0.2 to 0.5 parts of epoxy chain extender;

[0020] The middle layer comprises: 10 to 15 parts of modified montmorillonite, 5 to 10 parts of PLA, 10 to 25 parts of PBAT, 45 to 70 parts of PPC, and 0.2 to 0.5 parts of epoxy chain extender;

[0021] The inner layer comprises: 30-45 parts of PLA, 50-65 parts of PBAT, and 0.2-0.5 parts of epoxy chain extender; the inner layer may also comprise an optional opening agent, the amount of the opening agent is 2-5 parts,

[0022] The method for preparing the middle layer raw material for preparing the middle layer comprises: (i) dividing the epoxy chain extender used for the middle layer into two parts, epoxy chain extender A and epoxy chain extender B, and mixing PPC, modified montmorillonite and epoxy chain extender A to prepare a first middle layer masterbatch; (ii) mixing PLA, PBAT and epoxy chain extender B to prepare a second middle layer masterbatch; (iii) uniformly mixing the first middle layer masterbatch and the second middle layer masterbatch, and extruding and granulating to obtain the middle layer raw material.

[0023] The total thickness of the fully biodegradable composite film is 30-40 μm, and the thickness ratio of the outer layer, the middle layer and the inner layer is 1:(1-1.5):1.

[0024] Wherein, optionally, according to needs, the outer layer may further include 0 to 1.0 parts by weight of an antistatic agent.

[0025] Wherein, optionally, according to needs, the middle layer may further include 0 to 2 parts by weight of masterbatch.

[0026] Wherein, optionally, according to needs, the inner layer may further include 2 to 5 parts by weight of an opening agent SiO2.

[0027] The above-mentioned antistatic agent, masterbatch and SiO2 can all be commercially available products.

[0028] The PLA is polylactic acid with a weight average molecular weight of 100,000 to 250,000, preferably polylactic acid with a weight average molecular weight of 150,000 to 200,000, which has good film-forming properties and a wide processing range.

[0029] The PBAT is polybutylene adipate / terephthalate with a weight average molecular weight of 50,000 to 100,000, preferably polybutylene adipate / terephthalate with a moderate molecular chain, a certain degree of branching, and a weight average molecular weight of 50,000 to 75,000.

[0030] The PPC polypropylene carbonate has a number average molecular weight of 30,000 to 50,000, a molecular weight distribution of 3 to 6, a carbon dioxide content greater than 40%, and a density of 1.23 to 1.32. g / cm 3 . PPC with a number average molecular weight of 30,000 to 40,000 is preferred, which can give the packaging film good barrier properties and strong adhesion properties.

[0031] The epoxy chain extender may be a copolymer of one or more of cyclohexyl acrylate, glycidyl methacrylate, methyl methacrylate and styrene. The epoxy chain extender is preferably an epoxy chain extender that can reduce the regularity of PLA and increase the branching degree of PLA, preferably containing 7 to 10 active epoxy groups, an epoxy equivalent of 300-400 g / mol, a particle size of 0.5 to 1.5 mm, and a weight average molecular weight of 7000 to 8000; for example, BASF's ADR4468.

[0032] The modified calcium carbonate is an organic modified calcium carbonate, which is prepared by modifying commercially available calcium carbonate with a first organic modifier. The commercially available calcium carbonate is preferably a light calcium carbonate with a particle size of 700 to 1000 meshes and is white in color. The first organic modifier includes dioctadecyl dimethyl ammonium chloride.

[0033] The modified montmorillonite is an organic modified montmorillonite or an organic activated montmorillonite, which is prepared by modifying commercial bentonite with a second organic modifier. The commercial bentonite is preferably a sodium-based montmorillonite with a montmorillonite content greater than 30% by mass, a layer thickness of 0.90-1.5 nm (preferably 0.96 nm), an aspect ratio of 100 to 1000, and sodium ions are adsorbed between the layers. The second organic modifier includes dioctadecyl dimethyl ammonium chloride.

[0034] The present invention also provides a method for preparing the fully biodegradable film, comprising the steps of:

[0035] (1) preparing modified calcium carbonate: using a first organic modifier to organically modify calcium carbonate to obtain the modified calcium carbonate;

[0036] (2) preparing modified montmorillonite: using a second organic modifier to organically modify montmorillonite to obtain the modified montmorillonite;

[0037] (3) preparing the outer layer raw material: drying, stirring, and extruding and granulating the outer layer raw material, wherein the outer layer formula amount of modified calcium carbonate, PLA, PBAT, and epoxy chain extender is uniformly mixed to obtain the outer layer raw material;

[0038] (4) Preparation of middle layer raw materials:

[0039] (4.1) The epoxy chain extender used in the middle layer is divided into two parts: epoxy chain extender A and epoxy chain extender B. The middle layer formula amount of PPC, modified montmorillonite and epoxy chain extender A are mixed to prepare a middle layer first masterbatch;

[0040] (4.2) preparing a second middle layer masterbatch by mixing PLA, PBAT and epoxy chain extender B in a middle layer formula;

[0041] (4.3) mixing the first middle layer masterbatch and the second middle layer masterbatch uniformly, extruding and granulating, to obtain the middle layer raw material;

[0042] (5) preparing the inner layer raw material: drying, stirring, and extruding and granulating the inner layer formula amount of PLA, PBAT, epoxy chain extender, and optional opening agent to obtain the inner layer raw material;

[0043] (6) Blown film: The outer layer raw material, the middle layer raw material and the inner layer raw material are used to carry out three-layer co-extrusion blown film to obtain the fully biodegradable film.

[0044] Wherein, the preparation of modified calcium carbonate in step (1) specifically comprises:

[0045] (1.1) vacuum drying the calcium carbonate to obtain dried calcium carbonate;

[0046] (1.2) placing 10-50 parts by weight of the dried calcium carbonate into 100-1000 parts by weight of the first solution, mixing them evenly, to obtain a suspension A1;

[0047] (1.3) dissolving 0.1-3 parts by weight of the first organic modifier in 300-1200 parts by weight of the first solution, and mixing them uniformly to obtain a suspension A2;

[0048] (1.4) Ultrasonic dispersion is performed on the suspension A1. During the ultrasonic dispersion, the suspension A2 is slowly added dropwise to the suspension A1. The suspension is ultrasonically dispersed at 70-80° C. for 4-6 h (preferably 5 h) until the mixture is uniformly mixed. The modified calcium carbonate is obtained after suction filtration, drying and pulverization.

[0049] Wherein, in the step (1.1), the vacuum drying temperature is 75-90°C, the vacuum drying time is 2-6h (preferably 4h), the vacuum degree of vacuum drying is 0.08-0.12MPa (preferably 0.10MPa), and the vacuum drying can be performed in a vacuum oven;

[0050] Wherein, in the steps (1.2) and (1.3), the first solution is an aqueous solution of ethylene glycol, wherein the volume ratio of ethylene glycol to deionized water is 80-90:10-20 (preferably 85:15); and the mixing is performed by ultrasonic dispersion mixing for 20-40 minutes (preferably 30 minutes).

[0051] Wherein, in the step (1.4), the particle size of the modified calcium carbonate obtained is 10-20 μm.

[0052] Wherein, the preparation of modified montmorillonite in step (2) specifically comprises:

[0053] (2.1) Purifying commercially available montmorillonite: adding 1-50 parts by weight of commercially available montmorillonite to 100-1000 parts by weight of water, stirring at high speed at 50-80° C. to form a suspension system, removing the precipitate in the suspension system, and then adding 1-20 parts by weight of trichloroacetic acid to the suspension system, stirring evenly, to obtain a suspension B1;

[0054] (2.2) dissolving 0.1-10 parts by weight of a second organic modifier in 20-300 parts by weight of anhydrous ethanol to form a solution B2;

[0055] (2.3) Solution B2 is added dropwise to the suspension B1 at 70-90° C. with stirring, and the adding time is controlled within 0.5-3 h to obtain a modified montmorillonite suspension, which is then washed, filtered, dried, and crushed to obtain the modified montmorillonite.

[0056] Wherein, in the step (2.3), the particle size of the modified montmorillonite obtained is 50-150 μm.

[0057] Wherein, in the step (3), the drying comprises: drying in a vacuum drying oven at 60-80°C (preferably 70°C) for 3-5h (preferably 4h).

[0058] Wherein, in the step (3), the stirring comprises: stirring evenly in a low-speed stirrer, with a stirring speed of 500-1000 r / min, a stirring time of 5-10 min, and a stirring temperature of 10-20°C.

[0059] Wherein, in the step (3), the extrusion granulation comprises: using a twin-screw extruder with a length-to-diameter ratio (L / D) of 48-52 for extrusion granulation, and the granulation temperature is 150-170°C.

[0060] Wherein, the step (4.1) specifically comprises: first, placing PPC in a vacuum drying oven at 30-50°C (preferably 40°C) for vacuum drying for 36-60h (preferably 48h), and placing modified montmorillonite in a vacuum drying oven at 50-70°C (preferably 60°C) for vacuum drying for 36-60h (preferably 48h); then, placing the dried PPC, the dried modified montmorillonite and the epoxy chain extender A in a low-speed mixer and mixing them evenly, wherein the stirring speed is 500-800r / min, the stirring time is 5-10min, and the stirring temperature is 10-20°C; finally, using a twin-screw extruder with a length-to-diameter ratio (L / D) of 48-52 for extrusion granulation to obtain the middle-layer first masterbatch, wherein the granulation temperature is 120-140°C.

[0061] Wherein, the step (4.2) specifically comprises: first, placing PLA, PBAT and epoxy chain extender B in a vacuum drying oven at 60-80°C (preferably 70°C) for vacuum drying for 3-5h (preferably 4h); then, mixing the dried PLA, PBAT and epoxy chain extender B in a low-speed mixer, wherein the stirring speed is 500-1000r / min, the stirring time is 5-10min, and the stirring temperature is 10-20°C; finally, extruding and granulating using a twin-screw extruder with a length-to-diameter ratio (L / D) of 48-52 to obtain the middle-layer second masterbatch, wherein the granulation temperature is 150-170°C.

[0062] Wherein, the step (4.3) specifically comprises: first, placing the middle-layer first masterbatch and the middle-layer second masterbatch in a vacuum drying oven at 30-50°C (preferably 40°C) and a vacuum drying oven at 60-80°C (preferably 70°C) for vacuum drying for 3-5h (preferably 4h); then, mixing the dried middle-layer first masterbatch and the dried middle-layer second masterbatch in a low-speed mixer, wherein the stirring speed is 500-1000r / min, the stirring time is 5-10min, and the stirring temperature is 10-20°C; finally, using a twin-screw extruder with a length-to-diameter ratio (L / D) of 48-52 for extrusion granulation to obtain the middle-layer raw material, wherein the granulation temperature is 150-170°C.

[0063] Wherein, in the step (5), the drying comprises: drying in a vacuum drying oven at 60-80°C (preferably 70°C) for 3-5h (preferably 4h).

[0064] Wherein, in the step (5), the stirring comprises: stirring evenly in a low-speed stirrer, with a stirring speed of 500-1000 r / min, a stirring time of 5-10 min, and a stirring temperature of 10-20°C.

[0065] Wherein, in the step (5), the extrusion granulation comprises: using a twin-screw extruder with a length-to-diameter ratio (L / D) of 48-52 for extrusion granulation, and the granulation temperature is 150-170°C.

[0066] Among them, the step (6) specifically includes: passing the outer layer raw material, the middle layer raw material, and the inner layer raw material through three extruders respectively, entering the same three-layer film blowing die after being plasticized evenly, and being extruded from the die to form film bubbles after fusion to obtain the fully biodegradable film.

[0067] Compared with the prior art, the present invention has the following beneficial effects:

[0068] (1) The present invention uses fewer types of base materials, and the obtained fully biodegradable packaging film has good uniformity and quality.

[0069] (2) In the middle layer raw material of the present invention, the two-dimensional lamellar structure of montmorillonite is fully utilized, and the modified montmorillonite is prepared by cation exchange. The distance between the montmorillonite lamellars is increased while the microenvironment within the lamellars is improved, so that the organic long-chain dioctadecyl cations entering the lamellars effectively change the surface of the montmorillonite lamellars into lipophilic and hydrophobic properties, thereby reducing the surface energy between the lamellars, thereby allowing PPC to insert between the montmorillonite lamellars for reaction.

[0070] The PPC molecular chain contains carbonyl and ether bonds, and has high molecular chain mobility during the melting process. At the same time, part of the montmorillonite can be used as a nucleating agent to promote the heterogeneous nucleation of PPC, reduce spherulites, make the grains regular and smooth, and arrange them regularly between the montmorillonite layers, stack them tightly, increase air resistance, and improve gas barrier properties. The insertion of PPC also further increases the interlamellar spacing of montmorillonite, realizes the effective peeling of montmorillonite layers, and the middle-layer first masterbatch forms a disordered "PPC regularly arranged inserted" montmorillonite layered structure.

[0071] During the preparation of the second masterbatch in the middle layer, the special epoxy functional group structure of the epoxy chain extender effectively reduces the regularity of PLA and increases the branching degree of PLA. At the same time, low molecular weight PBAT is interspersed in it to form a "networked" structure.

[0072] When the first and second masterbatches of the middle layer are melt-blended, the disordered layered structure of "PPC regularly arranged inserted" montmorillonite is evenly distributed in the second masterbatch, and the entire composite material completely combines the complementary microstructures of inorganic materials and polymers, so that the disordered "PPC regularly arranged inserted" montmorillonite layered structure is arranged to form a dense protective layer similar to "PLA / PBAT matrix-MMT flakes-PPC regularly arranged-MMT flakes-PLA / PBAT matrix", which effectively blocks the flow of gas.

[0073] At the same time, due to the addition of chain extenders, the base materials have better compatibility, and the cross-networked structure of PLA and PBAT also makes the composite film have better impact resistance, puncture resistance and tear resistance.

[0074] (3) By adding calcium carbonate, a cheap and easily modifiable filler, to the outer layer, the overall strength of the composite film can be improved while the overall stacking performance of the composite film can be effectively improved.

[0075] (4) The three-layer film of the present invention uses PLA and PBAT as the matrix materials, and has strong adhesion between the layers. By adding different additives and fillers, the advantages of the three-layer film materials are comprehensively utilized, and the synergistic effect of "1+1+1>>3" can be exerted to improve the overall performance of the film. The prepared film has strong tear resistance, good impact resistance, can meet the high and low temperature use environment, and has good rigidity and toughness balance and barrier performance.

[0076] (5) The preparation method of the present invention is simple, and the granulation and film blowing of the three-layer raw materials can be completed using general extrusion equipment.

[0077] (6) The film prepared by the present invention can be used to prepare packaging films of different thicknesses according to actual needs, and can meet the needs of high-end packaging fields such as supermarket shopping bags, cargo express bags, packaging of high-tech precision instruments, food and pharmaceutical industries. DETAILED DESCRIPTION

[0078] The present invention will be described in further detail below in conjunction with specific embodiments. However, it should be understood that these embodiments are only for illustration and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims of the present application.

[0079] In the following examples, PLA was purchased from Natrueworks, USA; PBAT was purchased from Jinhui Zhaolong High-tech Co., Ltd.; PPC was purchased from Nanyang Zhongju Tianguan Low Carbon Technology Co., Ltd.; the epoxy chain extender brand is ADR4468, purchased from BASF, and other raw materials and reagents, unless otherwise specified, are raw materials and reagents that can be obtained from commercial channels such as conventional markets.

[0080] Examples 1-4

[0081] The fully biodegradable composite films of Examples 1-4 were prepared. The composition ratios of the components of each example are shown in Table 1 below. The weight percentage of each component is shown in the table.

[0082] Modified calcium carbonate, specifically calcium carbonate modified with dioctadecyl dimethyl ammonium chloride, in the subsequent tables, for example, 30 (1:100) in Example 1 means: the weight of the modified calcium carbonate in Example 1 is 30, and the weight ratio of dioctadecyl dimethyl ammonium chloride to calcium carbonate in the modified calcium carbonate is 1:100, and Examples 2-4 are similar;

[0083] The modified montmorillonite is specifically montmorillonite modified with dioctadecyl dimethyl ammonium chloride. In the subsequent tables, for example, 10 (1:50) in Example 1 means: the weight parts of the modified montmorillonite in Example 1 are 10, and the weight ratio of dioctadecyl dimethyl ammonium chloride to montmorillonite in the modified montmorillonite is 1:50, and Examples 2-4 are similar.

[0084] Table 1 Raw materials and proportions of Examples 1-4

[0085]

[0086]

[0087] The fully biodegradable composite membranes of Examples 1 to 4 above were prepared by the following method:

[0088] Embodiment 1:

[0089] (1) Preparation of organic modified calcium carbonate

[0090] The commercially available light calcium carbonate was dried in a vacuum oven at 75°C for 4 hours with a vacuum value of 0.10 MPa to obtain the dried calcium carbonate;

[0091] Weigh 10 parts of the dried calcium carbonate, place them in 100 parts of a mixed aqueous solution of ethylene glycol (the volume ratio of ethylene glycol to deionized water is 85:15), and ultrasonically disperse the mixed solution for 30 minutes to obtain a calcium carbonate suspension A1;

[0092] 0.1 parts of commercially available dioctadecyl dimethyl ammonium chloride was dissolved in 300 parts of ethylene glycol mixed solution (the volume ratio of ethylene glycol to deionized water was 85:15), and ultrasonically dispersed for 30 minutes to obtain a suspension A2 of dioctadecyl dimethyl ammonium chloride.

[0093] The suspension A1 was further ultrasonically dispersed, and the suspension A2 was slowly added dropwise to the suspension A1, and ultrasonically dispersed at 70°C for 5 hours until the mixture was uniformly mixed. The mixture was filtered, dried, and crushed to obtain 10 μm organic modified calcium carbonate (the weight ratio of dioctadecyl dimethyl ammonium chloride to calcium carbonate was 1:100).

[0094] (2) Preparation of modified montmorillonite:

[0095] The commercially available montmorillonite is purified and then organically activated, specifically:

[0096] 10 parts of montmorillonite were added to 100 parts of deionized water, and stirred at high speed at 50°C to form a suspension system, and the precipitate was removed. 1 part of trichloroacetic acid was added to the suspension, and stirred evenly to form a suspension B1 for use;

[0097] Dissolve 0.1 parts of dioctadecyl dimethyl ammonium chloride in 20 parts of anhydrous ethanol to form solution B2;

[0098] Solution B2 was added dropwise to suspension B1 at 70°C while stirring. The dropping time was controlled within 0.5 h to obtain a modified montmorillonite suspension. After washing, drying, and crushing, 50 μm modified montmorillonite (the weight ratio of dioctadecyl dimethyl ammonium chloride to montmorillonite was 1:50) was prepared.

[0099] (3) Preparation of outer layer raw materials:

[0100] According to the formula of Example 1 shown in Table 1, modified calcium carbonate, PLA, PBAT, and chain extender ADR4468 were vacuum dried in a vacuum drying oven at 70°C for 4 hours, mixed evenly in a low-speed mixer, with a stirring speed of 500 r / min, a stirring time of 5 minutes, and a stirring temperature of 10°C. The mixture was extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 48, and the granulation temperatures in zones 1-5 were 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain an outer layer raw material;

[0101] (4) Preparation of middle layer raw materials:

[0102] The epoxy chain extender used in the middle layer is divided into two parts: epoxy chain extender A and epoxy chain extender B. PPC is placed in a vacuum drying oven at 40°C for vacuum drying for 48 hours, and the modified montmorillonite is vacuum dried at 60°C for 48 hours. According to the formula of Example 1 shown in Table 1, epoxy chain extender A, PPC and modified montmorillonite are mixed uniformly in a low-speed mixer, with a stirring speed of 500 r / min, a stirring time of 5 min, and a stirring temperature of 10°C. A twin-screw extruder with a length-to-diameter ratio (L / D) of 48 is used for extrusion granulation, and the granulation temperatures of zones 1-5 are 120°C, 125°C, 130°C, 135°C and 140°C, respectively, to prepare a first masterbatch for the middle layer.

[0103] According to the formula of Example 1 shown in Table 1, epoxy chain extender B, PLA, and PBAT were placed in a vacuum drying oven at 70°C, vacuum dried for 4 hours, and mixed evenly in a low-speed mixer at a stirring speed of 500 r / min, a stirring time of 5 min, and a stirring temperature of 10°C. The mixture was extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 48, and the granulation temperatures in zones 1-5 were 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain a second masterbatch for the middle layer;

[0104] The first middle layer masterbatch and the second middle layer masterbatch are placed in a 40°C vacuum drying oven and a 70°C vacuum drying oven respectively, vacuum dried for 4 hours, mixed evenly in a low-speed mixer, with a stirring speed of 500 r / min, a stirring time of 5 min, and a stirring temperature of 10°C, and extruded and granulated by a twin-screw extruder with a length-to-diameter ratio (L / D) of 48, and the granulation temperatures of zones 1-5 are 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain a middle layer raw material;

[0105] (5) Preparation of inner layer raw materials:

[0106] According to the formula of Example 1 shown in Table 1, PLA, PBAT, epoxy chain extender ADR4468, and opening agent SiO2 were placed in a vacuum drying oven at 70°C for 4 hours, mixed evenly in a low-speed mixer, with a stirring speed of 500 r / min, a stirring time of 5 minutes, and a stirring temperature of 10°C. The mixture was extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 48, and the granulation temperatures in zones 1-5 were 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain the inner layer raw material;

[0107] (6) Blown film

[0108] The raw materials for the outer layer, middle layer and inner layer are passed through three extruders respectively, and after being plasticized evenly, they enter the same three-layer blown film die head, and after fusion, they are extruded out of the die head to form film bubbles, thereby preparing a fully biodegradable composite film with a total thickness of 30 μm and a thickness ratio of 1:1:1 among the outer layer, middle layer and inner layer.

[0109] Embodiment 2:

[0110] (1) Preparation of organic modified calcium carbonate

[0111] The commercially available light calcium carbonate was dried in a vacuum oven at 790°C for 4 hours with a vacuum value of 0.10 MPa to obtain the dried calcium carbonate;

[0112] Weigh 50 parts of the dried calcium carbonate, place it in 1000 parts of a mixed aqueous solution of ethylene glycol (the volume ratio of ethylene glycol to deionized water is 85:15), and ultrasonically disperse the mixed solution for 30 minutes to obtain a calcium carbonate suspension A1;

[0113] 3 parts of commercially available dioctadecyl dimethyl ammonium chloride were dissolved in 1200 parts of ethylene glycol mixed solution (the volume ratio of ethylene glycol to deionized water was 85:15), and ultrasonically dispersed for 30 minutes to obtain a suspension A2 of dioctadecyl dimethyl ammonium chloride.

[0114] The suspension A1 was further ultrasonically dispersed, and the suspension A2 was slowly added dropwise to the suspension A1, and ultrasonically dispersed at 80°C for 5 hours until the mixture was uniformly mixed. The mixture was filtered, dried, and crushed to obtain 20 μm organic modified calcium carbonate (the weight ratio of dioctadecyl dimethyl ammonium chloride to calcium carbonate was 1:200).

[0115] (2) Preparation of modified montmorillonite:

[0116] The commercially available montmorillonite is purified and then organically activated, specifically:

[0117] 50 parts of montmorillonite were added to 1000 parts of deionized water, and stirred at high speed at 80°C to form a suspension system, and the precipitate was removed. 20 parts of trichloroacetic acid were added to the suspension, and stirred evenly to form a suspension B1 for use;

[0118] Dissolve 10 parts of dioctadecyl dimethyl ammonium chloride in 00 parts of anhydrous ethanol to form solution B2;

[0119] Solution B2 was added dropwise to suspension B1 at 90°C while stirring. The dropping time was controlled within 3.0 hours to obtain a modified montmorillonite suspension. The modified montmorillonite of 150 μm (the weight ratio of dioctadecyl dimethyl ammonium chloride to montmorillonite was 1:100) was prepared through washing, drying, crushing and other procedures.

[0120] (3) Preparation of outer layer raw materials:

[0121] According to the formula of Example 2 shown in Table 1, modified calcium carbonate, PLA, PBAT, and chain extender ADR4468 were vacuum dried in a vacuum drying oven at 70°C for 4 hours, mixed evenly in a low-speed mixer, with a stirring speed of 1000 r / min, a stirring time of 10 min, and a stirring temperature of 20°C. The mixture was extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 52, and the granulation temperatures in zones 1-5 were 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain an outer layer raw material;

[0122] (4) Preparation of middle layer raw materials:

[0123] The epoxy chain extender used in the middle layer is divided into two parts: epoxy chain extender A and epoxy chain extender B. PPC is placed in a vacuum drying oven at 40°C for vacuum drying for 48 hours, and the modified montmorillonite is vacuum dried at 60°C for 48 hours. According to the formula of Example 2 shown in Table 1, epoxy chain extender A, PPC and modified montmorillonite are mixed uniformly in a low-speed mixer, with a stirring speed of 800 r / min, a stirring time of 10 min, and a stirring temperature of 20°C. A twin-screw extruder with a length-to-diameter ratio (L / D) of 52 is used for extrusion granulation, and the granulation temperatures of zones 1-5 are 120°C, 125°C, 130°C, 135°C, and 140°C, respectively, to prepare a first masterbatch for the middle layer.

[0124] According to the formula of Example 2 shown in Table 1, epoxy chain extender B, PLA, and PBAT were placed in a vacuum drying oven at 70°C, vacuum dried for 4 hours, and mixed evenly in a low-speed mixer at a stirring speed of 1000 r / min, a stirring time of 10 min, and a stirring temperature of 20°C. The mixture was extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 52. The granulation temperatures in zones 1-5 were 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain a second masterbatch for the middle layer.

[0125] The first middle layer masterbatch and the second middle layer masterbatch are placed in a 40°C vacuum drying oven and a 70°C vacuum drying oven respectively, vacuum dried for 4 hours, and mixed evenly in a low-speed mixer, with a stirring speed of 1000 r / min, a stirring time of 10 min, and a stirring temperature of 20°C. The mixture is extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 52, and the granulation temperatures in zones 1-5 are 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain a middle layer raw material;

[0126] (5) Preparation of inner layer raw materials:

[0127] According to the formula of Example 2 shown in Table 1, PLA, PBAT, chain extender ADR4468, and opening agent SiO2 were placed in a vacuum drying oven at 70°C for 4 hours, mixed evenly in a low-speed mixer, with a stirring speed of 1000 r / min, a stirring time of 10 min, and a stirring temperature of 20°C. The mixture was extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 52, and the granulation temperatures in zones 1-5 were 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain the inner layer raw material;

[0128] (6) Blown film

[0129] The raw materials for the outer layer, middle layer and inner layer are passed through three extruders respectively, and after being plasticized evenly, they enter the same three-layer blown film die head, and after fusion, they are extruded out of the die head to form film bubbles, thereby preparing a fully biodegradable composite film with a total thickness of 30 μm and a thickness ratio of 1:1.5:1 among the outer layer, middle layer and inner layer.

[0130] Embodiment 3:

[0131] (1) Preparation of organic modified calcium carbonate

[0132] The commercially available light calcium carbonate was dried in a vacuum oven at 80°C for 4 hours with a vacuum value of 0.10 MPa to obtain the dried calcium carbonate;

[0133] Weigh 35 parts of the dried calcium carbonate, place it in 500 parts of a mixed aqueous solution of ethylene glycol (the volume ratio of ethylene glycol to deionized water is 85:15), and ultrasonically disperse the mixed solution for 30 minutes to obtain a calcium carbonate suspension A1;

[0134] 2 parts of commercially available dioctadecyl dimethyl ammonium chloride were dissolved in 900 parts of ethylene glycol mixed solution (the volume ratio of ethylene glycol to deionized water was 85:15), and ultrasonically dispersed for 30 minutes to obtain a suspension A2 of dioctadecyl dimethyl ammonium chloride.

[0135] The suspension A1 was further ultrasonically dispersed, and the suspension A2 was slowly added dropwise to the suspension A1, and ultrasonically dispersed at 75°C for 5 hours until the mixture was uniformly mixed. The mixture was filtered, dried, and crushed to obtain 15 μm organic modified calcium carbonate (the weight ratio of dioctadecyl dimethyl ammonium chloride to calcium carbonate was 1:150).

[0136] (2) Preparation of modified montmorillonite:

[0137] The commercially available montmorillonite is purified and then organically activated, specifically:

[0138] 35 parts of montmorillonite were added to 500 parts of deionized water, and stirred at high speed at 65°C to form a suspension system, and the precipitate was removed. 15 parts of trichloroacetic acid were added to the suspension, and stirred evenly to form a suspension B1 for use;

[0139] Dissolve 0.1 to 10 parts of dioctadecyl dimethyl ammonium chloride in 20 to 300 parts of anhydrous ethanol to form solution B2;

[0140] Solution B2 was added dropwise to suspension B1 at 80°C while stirring. The dropping time was controlled within 2.0 h to obtain a modified montmorillonite suspension. After washing, drying, and crushing, a 400 μm modified montmorillonite (the weight ratio of dioctadecyl dimethyl ammonium chloride to montmorillonite was 1:75) was prepared.

[0141] (3) Preparation of outer layer raw materials:

[0142] According to the formula of Example 3 shown in Table 1, modified calcium carbonate, PLA, PBAT, and chain extender ADR4468 were vacuum dried in a vacuum drying oven at 70°C for 4 hours, mixed evenly in a low-speed mixer, with a stirring speed of 800 r / min, a stirring time of 8 minutes, and a stirring temperature of 15°C. The mixture was extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 50, and the granulation temperatures in zones 1-5 were 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain an outer layer raw material;

[0143] (4) Preparation of middle layer raw materials:

[0144] The epoxy chain extender used in the middle layer is divided into two parts: epoxy chain extender A and epoxy chain extender B. PPC is placed in a vacuum drying oven at 40°C for vacuum drying for 48 hours, and the modified montmorillonite is vacuum dried at 60°C for 48 hours. According to the formula of Example 3 shown in Table 1, epoxy chain extender A, PPC and modified montmorillonite are mixed uniformly in a low-speed mixer, with a stirring speed of 650 r / min, a stirring time of 8 min, and a stirring temperature of 15°C. A twin-screw extruder with a length-to-diameter ratio (L / D) of 50 is used for extrusion granulation, and the granulation temperatures of zones 1-5 are 120°C, 125°C, 130°C, 135°C, and 140°C, respectively, to prepare a first masterbatch for the middle layer.

[0145] According to the formula of Example 3 shown in Table 1, epoxy chain extender B, PLA, and PBAT were placed in a vacuum drying oven at 70°C, vacuum dried for 4 hours, and mixed evenly in a low-speed mixer at a stirring speed of 800 r / min, a stirring time of 8 min, and a stirring temperature of 15°C. The mixture was extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 50. The granulation temperatures in zones 1-5 were 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain a second masterbatch for the middle layer.

[0146] The first middle layer masterbatch and the second middle layer masterbatch are placed in a 40°C vacuum drying oven and a 70°C vacuum drying oven respectively, vacuum dried for 4 hours, and mixed evenly in a low-speed mixer at a stirring speed of 800 r / min, a stirring time of 8 min, and a stirring temperature of 15°C. The mixture is extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 50, and the granulation temperatures in zones 1-5 are 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain a middle layer raw material;

[0147] (5) Preparation of inner layer raw materials:

[0148] According to the formula of Example 3 shown in Table 1, PLA, PBAT, chain extender ADR4468, and opening agent SiO2 were placed in a vacuum drying oven at 70°C for 4 hours, mixed evenly in a low-speed mixer, with a stirring speed of 800 r / min, a stirring time of 8 minutes, and a stirring temperature of 15°C. The mixture was extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 50, and the granulation temperatures in zones 1-5 were 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain the inner layer raw material;

[0149] (6) Blown film

[0150] The raw materials for the outer layer, middle layer and inner layer are passed through three extruders respectively, and after being plasticized evenly, they enter the same three-layer blown film die head, and after fusion, they are extruded out of the die head to form film bubbles, thereby preparing a fully biodegradable composite film with a total thickness of 30 μm and a thickness ratio of 1:1.25:1 among the outer layer, middle layer and inner layer.

[0151] Embodiment 4:

[0152] (1) Preparation of organic modified calcium carbonate

[0153] The commercially available light calcium carbonate was dried in a vacuum oven at 80°C for 4 hours with a vacuum value of 0.10 MPa to obtain the dried calcium carbonate;

[0154] Weigh 30 parts of the dried calcium carbonate, place it in 300 parts of a mixed aqueous solution of ethylene glycol (the volume ratio of ethylene glycol to deionized water is 85:15), and ultrasonically disperse the mixed solution for 30 minutes to obtain a calcium carbonate suspension A1;

[0155] 1.5 parts of commercially available dioctadecyl dimethyl ammonium chloride were dissolved in 600 parts of ethylene glycol mixed solution (the volume ratio of ethylene glycol to deionized water was 85:15), and ultrasonically dispersed for 30 minutes to obtain a suspension A2 of dioctadecyl dimethyl ammonium chloride.

[0156] The suspension A1 was further ultrasonically dispersed, and the suspension A2 was slowly added dropwise to the suspension A1, and ultrasonically dispersed at 75°C for 5 hours until the mixture was uniformly mixed. The mixture was filtered, dried, and crushed to obtain an organic modified calcium carbonate of 12 μm (the weight ratio of dioctadecyl dimethyl ammonium chloride to calcium carbonate was 1:125).

[0157] (2) Preparation of modified montmorillonite:

[0158] The commercially available montmorillonite is purified and then organically activated, specifically:

[0159] 25 parts of montmorillonite were added to 250 parts of deionized water, and stirred at high speed at 60°C to form a suspension system, and the precipitate was removed. 12 parts of trichloroacetic acid were added to the suspension, and stirred evenly to form a suspension B1 for later use;

[0160] Dissolve 0.1 to 10 parts of dioctadecyl dimethyl ammonium chloride in 20 to 300 parts of anhydrous ethanol to form solution B2;

[0161] Solution B2 was added dropwise to suspension B1 at 75°C while stirring. The dropping time was controlled within 1.5 h to obtain a modified montmorillonite suspension. After washing, drying, and crushing, 85 μm modified montmorillonite (the weight ratio of dioctadecyl dimethyl ammonium chloride to montmorillonite was 1:65) was prepared.

[0162] (3) Preparation of outer layer raw materials:

[0163] According to the formula of Example 4 shown in Table 1, modified calcium carbonate, PLA, PBAT, and chain extender ADR4468 were vacuum dried in a vacuum drying oven at 70°C for 4 hours, mixed evenly in a low-speed mixer, with a stirring speed of 650 r / min, a stirring time of 7 minutes, and a stirring temperature of 12°C. The mixture was extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 50, and the granulation temperatures in zones 1-5 were 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain an outer layer raw material;

[0164] (4) Preparation of middle layer raw materials:

[0165] The epoxy chain extender used in the middle layer is divided into two parts: epoxy chain extender A and epoxy chain extender B. PPC is placed in a vacuum drying oven at 40°C for vacuum drying for 48 hours, and the modified montmorillonite is vacuum dried at 60°C for 48 hours. According to the formula of Example 4 shown in Table 1, epoxy chain extender A, PPC and modified montmorillonite are mixed uniformly in a low-speed mixer, with a stirring speed of 650 r / min, a stirring time of 7 min, and a stirring temperature of 12°C. A twin-screw extruder with a length-to-diameter ratio (L / D) of 50 is used for extrusion granulation, and the granulation temperatures of zones 1-5 are 120°C, 125°C, 130°C, 135°C and 140°C, respectively, to prepare a first masterbatch for the middle layer.

[0166] According to the formula of Example 4 shown in Table 1, epoxy chain extender B, PLA, and PBAT were placed in a vacuum drying oven at 70°C, vacuum dried for 4 hours, and mixed evenly in a low-speed mixer at a stirring speed of 700 r / min, a stirring time of 7 min, and a stirring temperature of 12°C. The mixture was extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 50. The granulation temperatures in zones 1-5 were 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain a second masterbatch for the middle layer.

[0167] The first middle layer masterbatch and the second middle layer masterbatch are placed in a 40°C vacuum drying oven and a 70°C vacuum drying oven respectively, vacuum dried for 4 hours, mixed evenly in a low-speed mixer, with a stirring speed of 700 r / min, a stirring time of 7 min, and a stirring temperature of 12°C, and extruded and granulated by a twin-screw extruder with a length-to-diameter ratio (L / D) of 50, and the granulation temperatures of zones 1-5 are 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain a middle layer raw material;

[0168] (5) Preparation of inner layer raw materials:

[0169] According to the formula of Example 4 shown in Table 1, PLA, PBAT, chain extender ADR4468, and opening agent SiO2 were placed in a vacuum drying oven at 70°C for 4 hours, mixed evenly in a low-speed mixer, with a stirring speed of 650 r / min, a stirring time of 6 minutes, and a stirring temperature of 15°C. The mixture was extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 50, and the granulation temperatures in zones 1-5 were 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain the inner layer raw material;

[0170] (6) Blown film

[0171] The raw materials for the outer layer, middle layer and inner layer are passed through three extruders respectively, and after being plasticized evenly, they enter the same three-layer blown film die head, and after fusion, they are extruded out of the die head to form film bubbles, thereby preparing a fully biodegradable composite film with a total thickness of 30 μm and a thickness ratio of 1:1.3:1 among the outer layer, middle layer and inner layer.

[0172] Comparative Example 1

[0173] According to the raw material ratio of Example 3, except that the preparation method of the middle layer raw material is different from that of Example 3, the remaining steps are the same as those of Example 3 to prepare the fully biodegradable composite film of Comparative Example 1.

[0174] The method for preparing the middle-layer raw material of Comparative Example 1 does not undergo two granulations, specifically: according to the middle-layer raw material formula of Example 3 shown in Table 1, PPC is placed in a vacuum drying oven at 40°C for 48 hours, and the modified montmorillonite, PLA, PBAT, and chain extender ADR4468 are placed in a vacuum drying oven at 70°C for 7 hours. All raw materials are mixed evenly in a low-speed mixer, with a stirring speed of 800r / min, a stirring time of 8min, and a stirring temperature of 15°C. A twin-screw extruder with a length-to-diameter ratio (L / D) of 50 is used for extrusion granulation, and the granulation temperatures of zones 1-5 are 120°C, 135°C, 140°C, 155°C, and 160°C, respectively, to obtain the middle-layer raw material by extrusion.

[0175] Comparative Example 2

[0176] According to the raw material ratio of Example 3, except that the preparation method of the middle layer raw material is different from that of Example 3, the remaining steps are the same as those of Example 3 to prepare the fully biodegradable composite film of Comparative Example 2.

[0177] In the method for preparing the middle layer raw material of Comparative Example 2, the organic modified montmorillonite of Example 3 is not used, but commercially available montmorillonite is directly used to prepare the masterbatch in two steps. The specific preparation method of the middle layer raw material is as follows:

[0178] According to the formula of Example 3 shown in Table 1 (except that the modified montmorillonite is replaced by commercial montmorillonite), PPC is placed in a vacuum drying oven at 40°C and vacuum dried for 48 hours. The commercial montmorillonite is vacuum dried at 60°C for 48 hours. The chain extender used in the middle layer is divided into two parts, chain extender A and chain extender B. Chain extender A, PPC and commercial montmorillonite are mixed evenly in a low-speed mixer at a stirring speed of 650r / min, a stirring time of 8min, and a stirring temperature of 15°C. A twin-screw extruder with a length-to-diameter ratio (L / D) of 50 is used for extrusion granulation. The granulation temperatures of zones 1-5 are 120°C, 125°C, 130°C, 135°C, and 140°C, respectively, to prepare the first masterbatch of the middle layer;

[0179] Chain extender B, PLA and PBAT were placed in a vacuum drying oven at 70°C for 4 hours, and mixed evenly in a low-speed mixer at a stirring speed of 750 r / min, a stirring time of 8 min and a stirring temperature of 15°C. The mixture was extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 50. The granulation temperatures in zones 1-5 were 150°C, 155°C, 160°C, 165°C and 170°C, respectively, to obtain a second masterbatch for the middle layer.

[0180] The first and second middle layer masterbatches were placed in a 40°C vacuum drying oven and a 70°C vacuum drying oven, respectively, and vacuum dried for 4 hours. The masterbatches were mixed evenly in a low-speed mixer at a stirring speed of 750 r / min, a stirring time of 8 min, and a stirring temperature of 15°C. The masterbatches were extruded and granulated using a twin-screw extruder with a length-to-diameter ratio (L / D) of 50. The granulation temperatures in zones 1-5 were 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain the middle layer raw material.

[0181] Comparative Example 3

[0182] According to the raw material ratio of Example 3, except that the preparation method of the middle layer raw material is different from that of Example 3, the remaining steps are the same as those of Example 3, and the fully biodegradable composite film of Comparative Example 3 is prepared.

[0183] In the method for preparing the middle layer raw material of Comparative Example 3, the timing of adding the modified montmorillonite in Example 3 was changed, and the mixing timing of other raw materials was adjusted. The specific method for preparing the middle layer raw material is as follows:

[0184] Weigh each raw material according to the raw material ratio of Example 3 shown in Table 1. Place PPC in a vacuum drying oven at 40°C and vacuum dry for 48 hours. Place chain extender ADR4468, PLA, and PBAT in a vacuum drying oven at 70°C and vacuum dry for 4 hours. Mix PPC, PLA, PBAT, and chain extender in a low-speed mixer, with a stirring speed of 800r / min, a stirring time of 8min, and a stirring temperature of 15°C. Use a twin-screw extruder with a length-to-diameter ratio (L / D) of 50 for extrusion granulation. The granulation temperatures in zones 1-5 are 120°C, 135°C, 140°C, 155°C, and 160°C, respectively. Extrusion produces the first masterbatch for the middle layer;

[0185] The above-mentioned middle layer first masterbatch and the modified montmorillonite prepared in Example 3 were placed in a vacuum drying oven at 60°C and vacuum dried for 4 hours. The first masterbatch and the organic modified montmorillonite were evenly mixed in a low-speed mixer with a stirring speed of 800r / min, a stirring time of 8min, and a stirring temperature of 15°C. A twin-screw extruder with a length-to-diameter ratio (L / D) of 50 was used for extrusion granulation. The granulation temperatures in zones 1-5 were 150°C, 155°C, 160°C, 165°C, and 170°C, respectively, to obtain the middle layer raw material by extrusion.

[0186] Comparative Example 4

[0187] According to the patent application with publication number CN 106633722 A, “A tear-resistant and high-toughness biodegradable material and its preparation method”, Example 6 in the specification of CN 106633722 A is used as Comparative Example 4 of the present invention.

[0188] The specific implementation method is as follows: accurately weigh 95kg of carbon nanotubes CNTS-5, heat to 80°C with a high-speed mixer, mix at high speed and add 5kg of KH-560 by spraying, mix for 20 minutes to obtain surface-treated nano carbon nanotubes CNTS-5. Accurately weigh 10kg of the surface-treated nano carbon CNTS-5 and 90kg of PBAT TH801, mix for 10 minutes with an internal mixer at 160°C and a speed of 40rpm, and then melt-mix with a single screw extruder with a length-to-diameter ratio of 40:1, the extrusion temperature is 160-170°C, and the screw speed is 800rpm to obtain PBAT / CNTS-5 one-step material. Accurately weigh 40kg of PLA 101, 30kg of PBAT / CNTS-5 one-step material, 15kg of acetyl epoxidized vegetable oil acid adipyl glyceride, 14.4kg of talc, 0.1kg of epoxy chain extender 4370, and 0.5kg of antioxidant 1076. The above components are pre-mixed uniformly, and melt-mixed by a twin-screw extruder. The temperature of the heating zone of the extruder from the feed port to the die is set to 130°C, 180°C, 180°C, 180°C, 180°C, 180°C, and 180°C in sequence, and the rotation speed is 200rpm to obtain a tear-resistant and high-toughness biodegradable material.

[0189] The prepared tear-resistant and high-toughness biodegradable material was placed in a vacuum drying oven at 70°C for 4 hours, and then passed through a single screw extruder with a length-to-diameter ratio of 25:1, a screw speed of 70-100 r / min, and an extrusion temperature of 150-175°C. Air was introduced into the blown film bubble from the head to inflate it, and the film bubble was cooled, shaped by a herringbone plate, and towed by a traction machine. Finally, it was flattened and rolled up by a winding device to prepare a biodegradable plastic film of Comparative Example 4 with a thickness of 30 μm.

[0190] Comparative Example 5

[0191] According to the patent application with publication number CN 109486138 A, "Modified PLA / PBAT biodegradable resin and preparation method thereof", Example 3 in the specification of CN 109486138 A is used as Comparative Example 5 of the present invention.

[0192] The specific implementation method is as follows: PHA-modified PLA / PBAT biodegradable resin is prepared from the following raw materials in parts by weight: 35 parts of PLA, 35 parts of PBAT, and 30 parts of PHA. The resin is formed into a film by a film blowing machine to prepare a biodegradable plastic shopping bag of Comparative Example 5 with a thickness of 30 μm.

[0193] Comparative Example 6

[0194] According to the patent application with publication number CN113881110 “A fully biodegradable composite film, preparation method and express bag thereof”, Example 4 in the specification with the best test performance was selected as Comparative Example 6 of the present invention.

[0195] Specifically, the composite film includes a first layer, a second layer and a third layer which are stacked in sequence; the first layer and the third layer include: 70 to 90 parts by weight of plasticized starch, 5 to 15 parts by weight of polylactic acid, 5 to 15 parts by weight of polycaprolactone and 0.02-0.1 parts by weight of a chain extender; the second layer includes: 60 to 80 parts by weight of polypropylene carbonate, 5 to 15 parts by weight of poly(adipate / terephthalate), 5 to 15 parts by weight of polycaprolactone and 0.02 to 0.1 parts by weight of a chain extender.

[0196] The prepared biodegradable material was placed in a vacuum drying oven at 70°C and vacuum dried for 4 hours, then passed through a single screw extruder with a length-to-diameter ratio of 25:1, a screw speed of 70-100 r / min, an extrusion temperature of 150-175°C, and air was introduced into the blown film bubble from the head to inflate it. The film bubble was cooled, shaped by a herringbone plate, towed by a traction machine, and finally flattened and rolled up by a winding device to prepare a biodegradable plastic film of Comparative Example 6 with a thickness of 30 μm.

[0197] Comparative Example 7

[0198] A biodegradable plastic shopping bag of a famous brand on the market with a thickness of 30 μm was purchased as Comparative Example 7.

[0199] Performance Testing

[0200] The biodegradable films obtained in the above examples and comparative examples were tested for performance, and the testing method was as follows:

[0201] The tensile strength, tensile yield stress and nominal strain at break were tested according to GB / T1040.3-2006, and the tensile rate was 200 mm / min.

[0202] Elmendorf tear strength: tested in accordance with GB / T 16578.2-2009, using rectangular specimens.

[0203] Puncture performance test: Cut the membrane into a circle with a diameter of 2.5 cm and stretch it on the mouth of a small triangular bottle. Use INSTRON to measure the pressure that the membrane can withstand, expressed as the maximum pressure per unit cross-sectional area (N / mm 2 ). The drill diameter is 13mm and the descending speed is 50mm / min.

[0204] Dart mass impact test: The dart mass impact test is carried out in accordance with the provisions of GB / T9639.1-2008A, using a single specimen, not the step method, and using a fixed dart mass to determine the number of undamaged samples. The dart mass is 50g and the number of samples is 10.

[0205] Heat resistance test: overlap two surfaces, apply a load of 4.9N on them, put them in an oven at 80℃ for 1 hour, take them out and immediately separate the two overlapping samples to check whether there are any abnormal conditions such as adhesion and melting marks on the surface.

[0206] Cold resistance test: Take 4 samples from the test film or bag, about 300mm long and 20mm wide. Put the other two samples in a -22℃ constant temperature box for more than 2 hours, take out the samples and fold them 180° in the length direction to check whether there are any damages, cracks or other abnormalities on the film surface.

[0207] Lifting test: Bag fatigue testing machine, amplitude 30mm±2mm, frequency 2~3Hz, put simulant (such as sand, rice grains, etc.) equivalent to the nominal load and with a volume not exceeding two-thirds of the effective solvent in the bag into the bag, and then hang it on the testing machine. Test 1800 times, observe the bag body and the bag for damage, and test 3 times.

[0208] Drop test: put a simulant (such as sand, rice grains, etc.) equivalent to the nominal weight and with a volume not exceeding two-thirds of the effective volume of the bag into the bag, remove the remaining air, seal the bag mouth with adhesive tape while keeping the upper bag film fully relaxed, and let the bag fall freely from a height of 0.5m above the bottom of the bag. The test ground should be a smooth, flat and hard ground, and observe whether the simulant (such as sand, rice grains, etc.) leaks out. The number of tests is 3.

[0209] Oxygen permeability: Referring to the national standard GB / T1038-2000, select film samples with intact surface, use matching film cutter to cut 4 kinds of films into circular samples with diameter of 960mm, put them into the oxygen permeability instrument, strictly seal, set the vacuum time to 2h, the temperature to 23℃, the pre-ventilation time to 15min, connect the air, and conduct air permeability performance test. Make 3 groups of parallel for each film, and take the average as the experimental result.

[0210] Water vapor transmission rate: refer to the national standard GB / T1037-1988, select film samples with intact surface, use matching film cutter to cut 4 kinds of films into circular samples with diameter of 800mm, put them into the moisture permeability instrument, the humidity in the test cup is 100%, the humidity in the test chamber is 10%, the temperature is raised and stabilized for 3 hours, and the moisture permeability performance test is carried out at 38℃. Three groups of parallel tests are carried out for each film, and the average is taken as the experimental result.

[0211] The fully biodegradable composite films prepared in Examples 1-4 meet the performance requirements of GB / T38082-2019 and GB / T21661-2020. Other performance results are shown in Table 2. The performance results of the biodegradable films prepared in Comparative Examples 1-7 are shown in Table 3.

[0212] Table 2 Performance test results of Examples 1-4

[0213]

[0214] Table 3 Performance test results of comparative examples 1-7

[0215]

[0216]

[0217] By comparing the test results of the embodiment and the comparative example, it can be seen that the standard test thickness of the biodegradable plastic shopping bag is 30 μm, and under the same test conditions:

[0218] (1) In Comparative Example 1, the middle layer raw material was prepared by one-step melt mixing, PPC was not effectively inserted into montmorillonite, and montmorillonite was not effectively stripped, the middle layer melt mixing effect was poor, the middle layer raw material did not form a dense protective layer, the prepared film had low physical properties, and poor barrier properties;

[0219] (2) In Comparative Example 2, the middle layer raw material was prepared by a two-step method by adding commercially available montmorillonite. The montmorillonite was not modified by ion exchange with dioctadecyl dimethyl ammonium chloride, the montmorillonite was not effectively stripped, and the PPC was not effectively inserted into the montmorillonite layer, resulting in the prepared film failing both the lifting and drop tests.

[0220] (3) In Comparative Example 3, PPC, PLA, and PBAT were first melt-blended and modified to prepare a first masterbatch, and then the modified montmorillonite prepared in the same manner as in Example was melt-blended in the second step, and finally a film was blown. PPC was not effectively inserted into the montmorillonite layers, and the effective isolation of the montmorillonite layers was not further promoted, and the middle layer raw materials were not prompted to form a dense barrier protective layer, resulting in poor barrier properties of the film;

[0221] (4) Comparative Example 4 is an example in CN 106633722 A. The carbon nanotubes are pretreated in the same way as in CN 106633722 A, and qualified special materials for degradable materials are prepared by two-step melt mixing. The biodegradable plastic shopping bag is prepared by the same film blowing process as in the present invention. Although the shopping bag has high tear strength and toughness, it has many added components and poor puncture ability. There are cracks in the cold resistance test, and there are damages in the drop test and the lifting test. At the same time, the film does not have barrier properties.

[0222] (5) Comparative Example 5 is an example in CN 109486138 A. The same method as CN 109486138 A is used to prepare a biodegradable plastic shopping bag. The raw material components are relatively simple, the price of PHA is relatively high, and the commercialization degree is low. In addition, PHA has low toughness, increased brittleness, poor puncture resistance, and fails the dart impact test. The prepared degradable plastic shopping bag is more sensitive to external temperature changes, fails both the cold resistance test and the heat resistance test, and has poor barrier properties.

[0223] (6) Comparative Example 6 is an example in CN113881110A, in which a fully biodegradable composite film is prepared by the preparation method in CN113881110A. Since the first and third layers use 70-90 parts by weight of plasticized starch, which is a relatively high ratio, the prepared film is difficult to meet the requirements of the lifting test and the drop test. The prepared composite film has poor adhesion between layers and poor physical properties.

[0224] (7) Comparative Example 7 is a biodegradable plastic shopping bag of a certain brand, which has good mechanical properties. However, it is consistent with the actual market usage. It is easy to be damaged when encountering hard objects. The overall puncture resistance of the shopping bag is poor. In addition, the barrier performance is poor, which is not suitable for high-end packaging applications.

[0225] The intermediate layer raw material of the embodiment of the present invention makes full use of the two-dimensional lamellar structure of montmorillonite, prepares modified montmorillonite by cation exchange, increases the interlamellar spacing of montmorillonite, and improves the microenvironment within the layer, so that the organic long-chain dioctadecyl cations entering the interlaminar effectively change the surface of the montmorillonite lamellae to lipophilic and hydrophobic, reducing the surface energy between the lamellae, so that PPC can be inserted between the montmorillonite lamellae for reaction, and the PPC molecular chain contains carbonyl and ether bonds, which have high molecular chain mobility during the melting process. At the same time, part of the montmorillonite can be used as a nucleating agent to promote heterogeneous nucleation of PPC, reduce spherulites, regular and smooth grains, and regularly arrange and closely stack between montmorillonite layers, increase air resistance, and improve gas barrier properties. The insertion of PPC also further increases the interlamellar spacing of montmorillonite, realizes the effective stripping of montmorillonite lamellae, and the first masterbatch in the middle layer forms a disordered "PPC regularly arranged inserted" montmorillonite layered structure. During the preparation of the second-step middle-layer masterbatch, the specific epoxy functional group structure of the chain extender effectively reduces the regularity of PLA and increases the branching degree of PLA. At the same time, the low molecular weight PBAT is interspersed therein to form a "networked" structure; the two masterbatches of the first and second steps of the middle layer are melt blended, and the middle layer "PPC regularly arranged inserted" montmorillonite layered structure is evenly distributed in the second masterbatch. The entire composite material completely combines the inorganic material and the polymer microstructure complementarity, so that the disordered "PPC regularly arranged inserted" montmorillonite layered structure is arranged to form a dense protective layer similar to "PLA / PBAT matrix-MMT layer-PPC regularly arranged-MMT layer-PLA / PBAT matrix", which effectively blocks the flow of gas. At the same time, due to the addition of the chain extender, the base materials have good compatibility, and the cross-networked structure of PLA and PBAT also makes the composite film have good impact resistance, puncture resistance and tear resistance. The outer layer raw material can improve the overall physical properties, stacking performance, and impact resistance of the composite film while reducing the production cost of the composite film by adding the inexpensive and easily modified filler calcium carbonate. The three layers of raw materials in the embodiment of the present invention all use PLA and PBAT as the matrix raw materials, and the layers have strong adhesion. By adding different additives and fillers, while comprehensively combining the advantages of the three-layer film raw materials, the synergistic effect of "1+1+1>>3" can be exerted to improve the overall performance of the film. The prepared film has strong tear resistance, good impact resistance, can meet high and low temperature use environments, and has good rigidity and toughness balance and barrier properties.

[0226] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0227] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

[0228] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A fully biodegradable composite film, comprising an outer layer, a middle layer and an inner layer arranged in sequence from the outside to the inside, wherein the thickness ratio of the outer layer, the middle layer and the inner layer is 1:(1-1.5):1; wherein, By weight: The outer layer comprises: 30 to 40 parts of modified calcium carbonate, 20 to 40 parts of PLA, 20 to 50 parts of PBAT, and 0.2 to 0.5 parts of epoxy chain extender; The middle layer comprises: 10 to 15 parts of modified montmorillonite, 5 to 10 parts of PLA, 10 to 25 parts of PBAT, 45 to 70 parts of PPC, and 0.2 to 0.5 parts of epoxy chain extender; The inner layer comprises: 30-45 parts of PLA, 50-65 parts of PBAT, and 0.2-0.5 parts of epoxy chain extender; The method for preparing the middle layer raw material for preparing the middle layer comprises: (i) dividing the epoxy chain extender used for the middle layer into two parts, epoxy chain extender A and epoxy chain extender B, and mixing PPC, modified montmorillonite and epoxy chain extender A to prepare a first middle layer masterbatch; (ii) mixing PLA, PBAT and epoxy chain extender B to prepare a second middle layer masterbatch; (iii) uniformly mixing the first middle layer masterbatch and the second middle layer masterbatch, and extruding and granulating to obtain the middle layer raw material.

2. The fully biodegradable composite film according to claim 1, wherein: The total thickness of the fully biodegradable composite film is 30-40 μm, wherein the thickness ratio of the outer layer, the middle layer and the inner layer is 1:(1-1.5):

1.

3. The fully biodegradable composite film according to claim 1, wherein: The PLA is polylactic acid with a weight average molecular weight of 100,000 to 250,000, the PBAT is polybutylene adipate / terephthalate with a weight average molecular weight of 50,000 to 100,000, the PPC polypropylene carbonate has a number average molecular weight of 30,000 to 50,000, a molecular weight distribution of 3 to 6, a carbon dioxide content of more than 40%, and a density of 1.23 to 1.32 g / cm 3 .

4. The fully biodegradable composite film according to claim 1, wherein: The epoxy chain extender is a copolymer of one or more of cyclohexyl acrylate, glycidyl methacrylate, methyl methacrylate and styrene.

5. The fully biodegradable composite film according to claim 1, wherein: The modified calcium carbonate is prepared by modifying commercially available calcium carbonate using a first organic modifier, wherein the first organic modifier includes dioctadecyl dimethyl ammonium chloride.

6. The fully biodegradable composite film according to claim 1, wherein: The modified montmorillonite is prepared by modifying commercially available bentonite with a second organic modifier, wherein the second organic modifier includes dioctadecyl dimethyl ammonium chloride.

7. The method for preparing a fully biodegradable film according to any one of claims 1 to 6, comprising the steps of: (1) preparing modified calcium carbonate: using a first organic modifier to organically modify calcium carbonate to obtain the modified calcium carbonate; (2) preparing modified montmorillonite: using a second organic modifier to organically modify montmorillonite to obtain the modified montmorillonite; (3) preparing the outer layer raw material: drying, stirring, and extruding and granulating the outer layer raw material, wherein the outer layer formula amount of modified calcium carbonate, PLA, PBAT, and chain extender is uniformly mixed to obtain the outer layer raw material; (4) Preparation of middle layer raw materials: (4.1) The epoxy chain extender used in the middle layer is divided into two parts: epoxy chain extender A and epoxy chain extender B. The middle layer formula amount of PPC, modified montmorillonite and epoxy chain extender A are mixed to prepare a middle layer first masterbatch; (4.2) preparing a second middle layer masterbatch by mixing PLA, PBAT and epoxy chain extender B in a middle layer formula; (4.3) mixing the first middle layer masterbatch and the second middle layer masterbatch uniformly, extruding and granulating, to obtain the middle layer raw material; (5) preparing inner layer raw materials: drying, stirring, and extruding and granulating the inner layer formula amount of PLA, PBAT, and epoxy chain extender to obtain the inner layer raw materials; (6) Blown film: The outer layer raw material, the middle layer raw material and the inner layer raw material are used to carry out three-layer co-extrusion blown film to obtain the fully biodegradable film.

8. The method for preparing a fully biodegradable film according to claim 7, wherein: The step (1) of preparing modified calcium carbonate specifically comprises: (1.1) vacuum drying the calcium carbonate to obtain dried calcium carbonate; (1.2) placing 10-50 parts by weight of the dried calcium carbonate into 100-1000 parts by weight of the first solution, mixing them evenly, to obtain a suspension A1; (1.3) dissolving 0.1-3 parts by weight of the first organic modifier in 300-1200 parts by weight of the first solution, mixing well, and obtaining a suspension A2; (1.4) Ultrasonic dispersion is performed on the suspension A1. During the ultrasonic dispersion, the suspension A2 is slowly added dropwise to the suspension A1. The suspension is ultrasonically dispersed at 70-80° C. for 4-6 hours until the mixture is uniformly mixed. The modified calcium carbonate is obtained after suction filtration, drying and pulverization.

9. The method for preparing a fully biodegradable film according to claim 7, wherein: The step (2) of preparing modified montmorillonite specifically comprises: (2.1) Purifying commercially available montmorillonite: adding 1-50 parts by weight of commercially available montmorillonite to 100-1000 parts by weight of water, stirring at high speed at 50-80° C. to form a suspension system, removing the precipitate in the suspension system, and then adding 1-20 parts by weight of trichloroacetic acid to the suspension system, stirring evenly, to obtain a suspension B1; (2.2) dissolving 0.1-10 parts by weight of a second organic modifier in 20-300 parts by weight of anhydrous ethanol to form a solution B2; (2.3) Solution B2 is added dropwise to the suspension B1 at 70-90° C. with stirring, and the adding time is controlled within 0.5-3 h to obtain a modified montmorillonite suspension, which is then washed, filtered, dried, and crushed to obtain the modified montmorillonite.

10. The method for preparing a fully biodegradable film according to any one of claims 7 to 9, wherein: The particle size of the modified montmorillonite is 50-150 microns, and the particle size of the modified calcium carbonate is 10-20 microns.

Citation Information

Patent Citations

  • Biological whole degrading film and mfg. process of its material

    CN100999587A

  • PLA / PBAT biodegradable composite material and preparation method thereof

    CN103254597A

  • Transparent, tear-resistant and biodegradable polylactic acid thin film and preparation method thereof

    CN104387732A

  • Full-degradable plastic film with wide using temperature range and strong toughness and manufacturing method thereof

    CN104893199A

  • Method for preparing PLA / PBAT / PPC composite modified material through reactive extrusion

    CN105038083A

Cited By

  • Humidity-control preservative film for fruits and vegetables and preparation method of humidity-control preservative film

    CN121375244A

  • High-transparency and high-barrier degradable film and preparation method thereof

    CN121424796A